Synthesis of (12R, 13S)-pyriculariol and (12R, 13S)-dihydropyriculariol revealed that the rice blast fungus, Pyricularia oryzae, produces these phytotoxins as racemates. Issue 1 (7th January 2021) - Nagashima, Yuta; Sasaki, Ayaka; Hiraoka, Ryoya; Onoda, Yuko; Tanaka, Koji; Wang, Zi-Yi; Kuwana, Atsuki; Sato, Yuki; Suzuki, Yuji; Izumi, Minoru; Kuwahara, Shigefumi; Nukina, Manabu; et al.
Abstract: Synthesis of assumed natural (12 R, 13 S )-enantiomers of pyriculariol (1 ) and dihydropyriculariol (2 ), phytotoxins isolated from rice blast disease fungus, Pyricularia oryzae, was achieved using Wittig reaction or microwave-assisted Stille coupling reaction as the key step. The synthesis revealed that the natural 1 and 2 are racemates. Foliar application test on a rice leaf indicated that both the salicylaldehyde core and side chain were necessary for phytotoxic activity. The fungus is found to produce optically active phytotoxins when incubated with rotary shaker, but racemic ones when cultured using an aerated jar fermenter. Graphical Abstract: